Measurements of Electric and Magnetic Fields due to Lightning Strokes Based on Single-station Detection - Wan Ismail, Ibrahim; Mohd Riduwan, Ghazali (2012)
A simple technique to determine the distance of the lightning strikes using single- station detection is described. The technique is based on ratio of the magnetics field to the electric field generated by the lightning stroke. A wire antenna was used to measure the electric field signals while magnetics loop antenna was used to measure the electromagnetics signal on the thunderstorm days. The LabVIEW software was used as a data logger to measure, analyze and calculate the lightning distance from the apparatus to the lightning stroke. The detection of the lightning activity using the developed system has been compared and validated to the Pekan Lightning Detection System (PLDS).